In vitro Differentiation of Melanocyte Stem Cells Derived from Vitiligo Patients into Functional Melanocytes - Vathsalya, Manchi; Shetty, Shricharith; Shetty, Nikhil; Shetty, Jayaprakasha; Shetty, Veena; Yeshwanth, Sunil Kumar; Patil, Prakash; Basavarajappa, Mohana Kumar (The Prodia Education and Research Institute (PERI), 2024)
BACKGROUND: Melanocyte stem cells (MelSCs) residing in the hair follicle bulge act as melanocyte reservoir for skin and hair, and may serve as an autologous source for treating vitiligo. Therefore, the study aimed to evaluate the in vitro differentiation ability of MelSCs derived from vitiligo patients into melanin-producing melanocytes for potential cellular therapy.METHODS: MelSCs from the vitiliginous (V-MelSCs), non-vitiliginous (NV-MelSCs) regions of vitiligo patients, as well as from control subjects (C-MelSCs) were established for evaluating their differentiation potential into melanin producing cells. The differentiation abilities were compared at the cellular and molecular levels. MelSCs were differentiated in vitro into induced-melanocytes (iMCs) by supplementing the culture medium with melanogenic factors. iMCs were analyzed by quantitative polymerase chain reaction (qPCR) for the expression of key melanogenic markers, including tyrosinase (TYR), tyrosinase-related protein 1 (TYRP1), dopachrome tautomerase (DCT), microphthalmia-associated transcription factor (MITF), c-KIT and S100. iMCs were also stained with L-DOPA to assess TYR activity in cells. Intracellular melanin content in iMCs was evaluated and compared among the vitiligo and control groups.RESULTS: MelSCs induced into iMCs displayed morphological changes with longer dendrites and prominent nuclei. iMCs stained positive for L-DOPA with an average intracellular melanin content of 30 pg/cell. iMCs expressed key melanogenic genes and the relative expression did not differ significantly among the groups.CONCLUSION: NV-MelSCs were unaltered by disease pathogenesis and capable of differentiating into melanocytes compared to V-MelSCs. Hence, these cells might offer a reliable source of melanocytes for vitiligo repigmentation therapy by autologous cellular transplantation.KEYWORDS: melanocyte stem cells, differentiation, melanocytes, vitiligo, in vitro